Investigation of structural phase transformation of Al metallic glass under uniaxial compression strain by molecular dynamics simulation - Kazanc, Sefa; Canbay, Canan Aksu (Springer Heidelberg, 2023)
In this study, the amorphous-crystalline structural phase transformations that occur as a result of uniaxial compression strain applied to the Al amorphous model system obtained by rapid cooling from the liquid phase at 100 K and 300 K temperature values were tried to be investigated by molecular dynamics (MD) simulation method. The forces acting on Al atoms were determined from the gradient of the Embedded Atom Method (EAM) potential function, which includes many-body interactions. The formation of bcc and hcp interphases was observed during the transformation from the amorphous phase to the fcc crystalline phase at a strain rate value of 1 x 10(9) s(-1). The evolution of atomic clusters with short-range order during the amorphous-crystal transformation was determined by radial distribution function (RDF), common neighbor analysis (CNA) and voronoi-polyhedra (VP) analysis, and the development of dislocations formed in the structure during the transformation was determined using DXA analysis. Amorphous-fcc-bcc-fcc and amorphous-bcc-fcc solid-solid phase transformations were determined for the model system at 300 K temperature and amorphous-fcc-bcc-fcc was determined by the applied compression strain. It was determined that the percentage of fcc unit cell structures was higher at 100 K temperature than 300 K temperature value.
Keywords: Metallic glass; Solid-solid phase transformation; Molecular dynamics; Voronoi polyhedron analysis